Response of microzooplankton community to the hydrographical transformations in the coastal waters off Kochi, along the southwest coast of India. (1st September 2018) - Anjusha, A.; Jyothibabu, R.; Jagadeesan, L.
Abstract: The response of microzooplankton to the hydrographical transformations in the coastal waters off Kochi, along the South-west coast of India, has been presented in this study. Sampling was carried out during January–December 2014 at four locations along a transect up to a depth of 30 m perpendicular to the Kochi coastline. Seasonal hydrographical features in the study region were chiefly influenced by two processes – estuarine flux in the surface layers and coastal upwelling in the subsurface layers. Coastal upwelling prevailed during the Southwest Monsoon, but its impact was impeded in the surface waters by the estuarine influx. Relatively high phytoplankton biomass was obtained in the offshore locations during the Southwest Monsoon which was primarily associated with the coastal upwelling. On the other hand, in the near-shore locations, plankton production was mainly associated with the high-nutrient, low-saline estuarine plume water. During the Southwest Monsoon, high estuarine influx and phytoplankton biomass led to increased abundance of microzooplankton community in the surface waters. The abundance of microzooplankton was low during the pre-monsoon, which seems to be impacted by the high top-down control of carnivorous copepods. A total of 59 species of microzooplankton were identified, of which 49 were species of ciliates and 10 were heterotrophic dinoflagellates. This study reveals the important role of aloricate ciliates in the coastal waters off Kochi, which was hitherto unknown. The overall results suggest the existence of a multivorous food web in the study region, which could be a general feature along the west coast of India. Highlights: Microzooplankton in relation to the seasonal hydrography in a tropical coastal water has been presented. Aloricate ciliates were found to be the dominant microzooplankton community. Microzooplankton community was significantly influenced by the estuarine flux and coastal upwelling. Surface and subsurface microzooplankton responded differently to the seasonal hydrographical changes.